2007
DOI: 10.1002/ptr.2119
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of ergosterol peroxide against Mycobacterium tuberculosis: dependence upon system and medium employed

Abstract: Ergosterol peroxide, cycloart-23-en-3beta,25-diol, vanillin and 4-hydroxybenzaldehyde have been isolated and characterized from a crude methanol extract of Euphorbia lagascae. Previous studies have shown contradictory results about the antibacterial activity of ergosterol peroxide against Mycobacterium tuberculosis. In order to clarify this question, the activity of this compound was tested against Mycobacterium tuberculosis H37Rv ATCC 27294 strain using two different systems: BACTEC 460TB (Bactec 460) and BAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Additional biological activities of ergosterol peroxide have been reported, i.e., antioxidant (Kim et al 1999), antimycobacterial (Cantrell et al 1999;Akihisa et al 2005;Duarte et al 2007), antiplasmodial (Kuria et al 2002), leishmanicidal activity (Correa et al 2006), antiinflammatory (Yasukawa et al 1996;Gao et al 2007;Kobori et al 2007), immunosuppressive (Kuo et al 2003), anti-atherosclerosis (Kim et al 2005) and aldose-reductase inhibitory activity (Lee et al 2006). Aside from the reported biological activities, we found that ergosterol peroxide had an effect on in vitro insect cells and an insecticidal activity against 3rd instar S. litura larvae via topical application.…”
Section: Discussionmentioning
confidence: 67%
“…Additional biological activities of ergosterol peroxide have been reported, i.e., antioxidant (Kim et al 1999), antimycobacterial (Cantrell et al 1999;Akihisa et al 2005;Duarte et al 2007), antiplasmodial (Kuria et al 2002), leishmanicidal activity (Correa et al 2006), antiinflammatory (Yasukawa et al 1996;Gao et al 2007;Kobori et al 2007), immunosuppressive (Kuo et al 2003), anti-atherosclerosis (Kim et al 2005) and aldose-reductase inhibitory activity (Lee et al 2006). Aside from the reported biological activities, we found that ergosterol peroxide had an effect on in vitro insect cells and an insecticidal activity against 3rd instar S. litura larvae via topical application.…”
Section: Discussionmentioning
confidence: 67%
“…Its well-known diastereomer ergosterol is a major sterol of the fungal cell membrane with significant pharmacological activities (Yuan et al 2006;Duarte et al 2007). Nectriafurone-8-methyl ether (2) (Tatum et al 1987b) was obtained as a yellowish solid.…”
Section: Resultsmentioning
confidence: 99%
“…This compound has demonstrated anti-inflammatory [39], anti-bacterial [40], anti-atherosclerosis [41], and anti-proliferative properties in human T cells [42]. Its ability to induce death in a number of cancer cell lines shed light on its potential clinical use in cancer patients.…”
Section: Resultsmentioning
confidence: 99%